Percepcões dos estudantes do Ensino Médio sobre Direitos Humanos - Monteiro, Hiatanderson da Silva (2025)
This research focuses on the perceptions and experiences of high school students regarding Human Rights, since understanding these understandings underpins the implementation of methodological strategies in Human Rights Education. The general objective of the research is to understand the perception of high school students from a full-time public school regarding human rights, highlighting their contribution to the formation/citizenship education of young people. This general objective is divided into the following specific objectives: a) Discuss the historical complexity that permeates the construction of Human Rights Education; b) Analyze the historical clash of neoliberal perspectives and their impacts on educational policies and pedagogical practices; c) Identify students' perceptions of human rights, seeking to understand the different understandings; d) Identify the forms of violence that configure human rights violations in the school environment; and e) Discuss, from the perspective of students, which methodological strategies can be applied in the teaching-learning process in and for Human Rights. In this proposition, this study had the empirical field as a basic methodological element, having as the locus of research, a Comprehensive Citizen School (ECI) of High School, located in the municipality of São José do Bonfim, sertão of Paraíba. This is an interdisciplinary research with a qualitative approach, using semi-structured interviews and focus groups as instruments for data collection, conducted through direct contact with 08 (eight) students who are in the 2nd or 3rd year of the aforementioned school, selected in a non-probabilistic and criterial manner. For the analysis and interpretation of the data, content analysis by thematic categorization was chosen. The results of the research indicate that the students understand human rights as synonymous with freedom and equality, embodying social rights, rights and duties of the citizen. In this path, violations of human rights in the school environment were evoked, intrinsically linked to a "lived world", which has the body as a kind of thermometer of violence, especially for bodies that do not fit into the structural standards of beauty. In this research, intersectionalities emerge: race and gender as intersections of violence, in addition to demands for the adoption of methodological strategies that dialogue with the interests, rhythms and ways of being of young people, who are, in many cases, placed in the place of silencing their voices.